Considerations in Management of Acute Otitis Media in the COVID-19 Era. (May 2021) - Mohan, Suresh; Workman, Alan; Barshak, Miriam; Welling, D. Bradley; Abdul-Aziz, Dunia
Objectives: To present the otologic findings of a patient with COVID-19 and complicated acute otitis media, evaluate for the presence of SARS-CoV-2 in middle ear fluid, and assess whether suctioning of middle ear fluid may be aerosol- generating. Methods: The case of a man with SARS-CoV-2 infection and complicated acute otitis media with facial paralysis is presented to illustrate unique clinical decisions made in context of the COVID-19 pandemic. A cadaveric temporal bone was used to simulate droplet spread during suctioning of fluorescein-labelled middle ear fluid and visualized with a blue-light filter. Results: A 23-year-old male who presented with complicated acute otitis media with facial paralysis was found to have an acute infection with SARS-CoV-2, with positive viral PCR of nasopharyngeal swab, and a negative PCR of the middle ear fluid. He was placed on isolation precautions and treated with myringotomy, topical and systemic antibiotics, and antivirals. Consistent with observations during endonasal suctioning, suctioning of middle ear fluid was not found to be aerosol or droplet generating. Conclusion: The case of a patient with active COVID-19 presenting with complicated acute otitis media in whom middle ear fluid was sampled to evaluate the etiology of the infection and the potential middle ear predilection of SARS-CoV-2 is described. This study has implications for the clinical management of patients with both known and unknown SARS-CoV-2 infection who present with ear disease. While middle ear suctioning may not be aerosol-generating, the risk of coughing or prolonged close contact requires heightened precautions during otologic procedures in patients with suspected or confirmed COVID-19.